Pengaruh Perlakuan Penggaraman Terhadap Sifat Fisikokimia Kimchi Mentimun - Nurjannah, Nurjannah; Chairiyah, Nurul; egra, saat; Ismandari, Titik; Pudjiwaty, Eko Hary; Hasriyuni, Hasriyuni (Universitas Teuku Umar, 2025)
Kimchi is an agricultural product made form fermented vegetables. Kimchi can be made with various types of vegetables such as Chinese cabbage, green mustard greens, cabbage, cucumber, radish and various other vegetables. Currently, kimchi is not only popular in Korea but also in other countries, including Indonesia. It is because kimchi contained high health benefits so that increasingly popular among Indonesian people. Fermentation gives kimchi its unique taste and texture. Tasted of kimchi dominated by acid which is lactic acid from fermentation by Lactic Acid Bacteria (LAB). Produced lactic acid can lower the pH and increase the sour taste. The lactic acid fermentation process will be perfect if the factors that influence the growth of lactic acid bacteria can be properly controlled. Factors that influence lactic acid bacteria growth are fermentation temperature, salt levels and the presence of nutrients. Determining the quality of kimchi is based on taste, nutritional value and food safety. Determination of organoleptic values was carried out by untrained respondents. Determination of nutritional value is carried out by chemical content analysis in the laboratory. The fermentation process is strongly influenced by the environment and growth substrate. Therefore, sometimes kimchi that made with the same ingredients can produce different tastes and qualities. In determining the right quality of kimchi, various tests are needed based on existing standards. These standards cover physical, chemical and organoleptic properties. From research it is known that the type of salt has an influence on water content values (25, 390), vitamin C levels (12,725), and lactic acid (28, 21246). The use of fine salt causes the water content and vitamin C values to be low. A higher salt concentration causes the salt, vitamin C and lactic acid levels to be higher as well. Meanwhile, based on organoleptic tests, the kimchi in the K4G1 treatment was the kimchi most liked by the panelists